Supercritical Technology Applied to Food, Pharmaceutical and Chemical Industries (MDPI - Multidisciplinary Digital Publishing Institute, 2024)
Supercritical-fluid-based technologies have emerged as unit operations in the chemical industry in the last few decades and have been selected as the answer to current demands for sustainability in industrial processing. The following Special Issue contains updated experimental research and comprehensive reviews on the use of different techniques involving supercritical fluids and pressurized liquids, including extraction, chemical reactions, encapsulation, and sterilization.